If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 7x) = 118 (3 * 2 + 7x * 2) = 118 (6 + 14x) = 118 Solving 6 + 14x = 118 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 14x = 118 + -6 Combine like terms: 6 + -6 = 0 0 + 14x = 118 + -6 14x = 118 + -6 Combine like terms: 118 + -6 = 112 14x = 112 Divide each side by '14'. x = 8 Simplifying x = 8
| 10+7*4=38 | | 3n+7n-4= | | 5y-25=99+y | | -8+4u=-32 | | 432/2/4325/34435 | | 4x+51=6x+9 | | 2n+7-n+2= | | x+7x-5= | | 56=6h | | 6y-25=95+y | | 24=c-8 | | 4x+7=23+2x | | 40+3x+20+x=180 | | https://homebase.schoolnet.com/files/assess_files/cf1ae17e-8d5e-4dca-981c-c9ee7af1d787/_s_I373865_1.png | | 6-7a-14=8+a | | 4x+81=13x+36 | | 9+2j=17 | | 7x+5-3y=-31 | | 12x-19y+27=1 | | 6(x-5)-3w=12 | | 3x+3*5=27 | | 10=4+3s | | 4x^3-15x^2-25x= | | -114=-2x+3(4x+2) | | 9+-1y+2y=14 | | w+19=40 | | -5c+2=4x+29 | | 7x+3x+9=5x+34 | | 7(5-z)=56 | | 10x-.66(9x+6)=4x-23 | | 3(x+50)-10=2(x+20) | | -7(2x+5)=2(-7x+10) |